Hydrocolloids in food processing - Laaman, Thomas (IFT Press series (Institute of Food Technologists series), 2010)
In Hydrocolloids in Food Processing, a group of the most experienced and impartial experts explains what stabilizers should be used and how they should be used, food product by food product. Numerous actual product formulations are packed into each chapter and the processing procedures to make these formulations are clearly described